Applications of the variance orientation transform method to the multiscale characterization of surface roughness and anisotropy - Wolski, Marcin; Podsiadlo, Pawel; Stachowiak, Gwidon (Pergamon, 2010)
There is no generally accepted method that could provide a full description of 3D surface topography (ST). Most of the currently used methods work well with isotropic surfaces at a single scale. Recently new method, called a variance orientation transform (VOT), has been developed for ST characterization. In this work, the usefulness of the VOT and its sensitivity to minute changes in ST have been tested. Images of real engineering surfaces, surfaces of adhesive wear particles and trabecular bone were used for the tests. The results obtained show that the VOT can be useful in both engineering and medical applications.